Factors predicting bacterial meningitis in children aged 6-18 months presenting with first febrile seizure - Khosroshahi, Nahid; Kamrani, Kamyar; Zoham, Mojdeh Habibi; Noursadeghi, Hamidreza (International Journal of Contemporary Pediatrics, 2016)
Background: Febrile seizures are the most common form of childhood seizure disorder. Between 2% and 5% of children between the age of 6 and 60 months experience at least one febrile seizure. Most of these febrile seizures are benign and self-limiting. However, some may indicate an underlying pathology like bacterial meningitis. As bacterial meningitis can be the most serious etiology of febrile seizures, we performed a cross sectional study to assess the factors predicting the risk of bacterial meningitis among various subgroups of young children with a first febrile seizure. Methods: In this cross sectional study, 571 infants aged between 6-18 months presenting with first simple seizure from September 2011 to September 2013 were enrolled. These patients were admitted to the neurology ward of Bahrami Children Hospital, a tertiary children hospital. All clinical data of the patients were analyzed. Results: Lumbar puncture was performed in 458 out of 571 patients (80.2 %). Bacterial meningitis was evident in 1.1% of patients with first febrile seizures. Eighty percent of children with bacterial meningitis were presented with complex febrile seizures with focal features. Another risk factor predicting bacterial meningitis was duration of postictal drowsiness. Conclusions: It seems that according to new data describing limited need of performing lumbar puncture in all children with febrile seizure, some predicting factors of bacterial meningitis can be used to prevent unnecessary lumbar puncture. Complex febrile seizures especially those with focal features are the most important predicting factors. Larger prospective studies are needed to assess the presumed conclusion.